PENGGUNAAN PRODUK KOSMETIK PEMUTIH WAJAH (WHITENING) Merek Pond’s (Pada Warga Kelurahan Sukasari Tangerang RW 04) - Susanti Susanti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Have White skin is one of the many beatiful caterigories that are ideal for every teenagers. This study aim to determine the using of facial whitening cosmetic produts in young women. This study was conducted on resident of RW 04 Sukasari Village Tangerang. Cosmetic product use are cosmetic products for facial whitening. Teenage daughter of RW 04 Sukasari Village Tangerang use pond’s brand whitening cosmetic productswhich suiteble for their skin.